Acupuncture Inhibits Morphine Induced-Immune Suppress via Antioxidant System. (22nd October 2022) - Zhao, Rong Jie; Lee, Dae Geon; Park, Chan Sik; Yang, Chae Ha; Kim, Hee Young; Lee, Mi Young; Song, Chang-Hyun; Cho, Il Je; Chan Kim, Sang; Ku, Sae Kwang; Lee, Bong Hyo
Abstract : Objectives . A powerful analgesic called Morphine causes addiction behaviors and immune suppression as a potential oxidative stressor. Acupuncture showed to inhibit oxidative stress-induced hepatic damage, regulate reactive oxygen species, and attenuate morphine addiction behaviors. Therefore, we investigated the potential effects of acupuncture on morphine-induced immune suppression. Materials and Methods . Rats received morphine intravenously through implanted catheters for 3, 7, or 21 days to determine the optimal condition for morphine-induced immune suppression. Second, we examined whether intravenous (iv.) or intraperitoneal (ip.) administration produced different results. Third, the effects of acupuncture in rats who received morphine for 21 days were investigated. Spleen and submandibular lymph node (S-LN) weights and natural killer (NK) cell activity were measured, and the white pulp diameter, total and cortical spleen thicknesses, and the number of lymphoid follicles in S-LNs were examined. The number of immunoreactive cells was also measured. Results . Decreased organ weights and increased atrophic changes were observed as morphine-induced immune suppression. However, dose-dependent increased immune suppression was not observed between 5.0 mg/kg and 10.0 mg/kg of morphine. And, 3-day withdrawal did not affect. Similar histopathological findings were observed in 5.0 and 10.0 ip. rats when compared to equal dosages of iv., respectively. The morphine induced-immune suppression evidenced by spleen and left S-LN weights, splenic NK cell activities, histopathological findings, and the immunoreactive cell number were normalized by acupuncture. Conclusion . These results indicate that acupuncture inhibits morphine-induced immune suppression, maybe via antioxidative action.